Percentage of the bycatch and discard composition in artisanal bottom trap fisheries - Nofrizal Nofrizal; Afni Afriani; Deni Efizon; Romie Jhonnerie (Depik, 2022)
Data on bycatch in the fishing effort required to manage fisheries resources. Unfortunately, the data on small-scale and traditional fisheries is still lacking. It makes it challenging to make fishing policies and regulations. Survey activities and experimental fishing were conducted to determine and analyze the composition of the main catch, bycatch and discarded by the local fisher's bottom traps in Sibolga, North Sumatra, Indonesia. Five units of the trap with a size of 150 cm x 100 cm x 50 cm (length x width x height) were used to collect fish data. These five trap units operated in the fishing ground, where local fishers usually operate their fishing gear. The fishing operation carried out within 1 mile of the coastline with water depths ranging from 7-10 meters. The duration of trap setting around 5-7 days for each fishing operation. A motorboat operated with a weight of 5.8 GT. The results showed that the total bottom trap catch consisted of 329 individuals with a total weight of 151.4 kg and 12 demersal fish species. The main catch was 148 individuals (88.9 kg), or 44.7% of the total catch during the experiment i.e. Chepalapholis urodeta, Ephinephelus areolatus, Epinephelus chlorostigma, Plectropomus leopardus, Ephinepelus coioides, Lates calcarifer, Lutjanus malabaricus, and Lutjanus erytropterus. The bycatch was 151 individuals (57.1 kg) or 46.1% i.e. Lethrinus obsoletus, Lutjanus ehrenbergii, Acanthurus auranticavus, Platax teira, Nemipterus japonicus, Scarus rivulatus, Lutjanus johnii, Siganus canaliculatus, Caesio cuning, and Taeniura lymma.While the discarded catch amounted to 30 individuals (5.4 kg) or 9.2% i.e. Naso brevirostris, Diodon holocanthus, and Diadema setosum. The bycatch utilization obtained by fishers was 83.4%, and the unutilized was 16.6%. The percentage of fish sizes worthy for consumption was 135 individuals (74.6%), and the size unworthy for consumption was 46 individuals (25.4%).Keywords:Fishing groundFishing gear Fishing operation Main catchTrap